Effect of High-Flow Nasal Cannula Oxygen Therapy in Immunocompromised Subjects With Acute Respiratory Failure - Kang, Hanyujie; Zhao, Zhiling; Tong, Zhaohui (Respiratory care, 2020)
Various studies have been performed to examine the effect of high-flow nasal cannula (HFNC) in immunocompromised patients with acute respiratory failure (ARF). However, the results were inconsistent. Thus, we conducted a meta-analysis to evaluate the effect of HFNC oxygen therapy in immunocompromised patients with ARF versus conventional oxygen therapy and noninvasive ventilation (NIV). Relevant studies published prior to May 11, 2019, were systematically searched. The primary outcome was intubation rate; secondary outcomes were mortality (ICU mortality, in-hospital mortality, and 90-d mortality) and ICU-acquired infections. Data were pooled using the random effects model. Of 832 identified studies, 8 were eligible for inclusion in our analysis ( = 2,167 subjects). HFNC was associated with lower intubation rates compared to conventional oxygen therapy (risk ratio [RR] 0.89, 95% CI 0.79-1.00, = .040), but we found no significant difference in the rate between HFNC and NIV (RR 0.74, 95% CI 0.46-1.19, = .22). We also found that HFNC did not increase the risk of ICU-acquired infections (RR 0.86, 95% CI 0.63-1.18, = .35). However, in comparison to other noninvasive therapies, HFNC exhibited no differences in ICU mortality (RR 0.82, 95% CI 0.58-1.17, = .28), in-hospital mortality (RR 0.92, 95% CI 0.74-1.15, = .48), or 90-d mortality (RR 0.98, 95% CI 0.81-1.18, = .82). Our results suggest that HFNC may be a feasible alternative to NIV, with lower intubation rates and no increased risk for ICU-acquired infections compared to standard oxygen therapy. However, HFNC did not appear to reduce mortality in immunocompromised subjects with ARF compared with other noninvasive therapies. Further high-quality randomized controlled trials should be performed to confirm these findings.